2000
DOI: 10.1128/jvi.74.23.11001-11007.2000
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of CCR5 Expression by CD4+T Cells in Lymphoid Tissues during Simian Immunodeficiency Virus Infection

Abstract: Early viral replication and profound CD4؉ T-cell depletion occur preferentially in intestinal tissues of macaques infected with simian immunodeficiency virus (SIV). Here we show that a much higher percentage of CD4 ؉ T cells in the intestine express CCR5 compared with those found in the peripheral blood, spleen, or lymph nodes. In addition, the selectivity and extent of the CD4 ؉ T-cell loss in SIV infection may depend upon these cells coexpressing CCR5 and having a "memory" phenotype (CD45RA ؊ ). Following in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
204
3
3

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 217 publications
(226 citation statements)
references
References 34 publications
16
204
3
3
Order By: Relevance
“…Finally, most DP cells in the intestine are memory cells. Memory CD4 + T cells have been shown to be selectively infected in SIV and HIV [1,[40][41][42]. Combined these observations support our earlier data suggesting that DP T cells in the intestine are rapidly eliminated in early SIV infection due to their increased expression of viral co-receptors and their higher level of activation [1].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Finally, most DP cells in the intestine are memory cells. Memory CD4 + T cells have been shown to be selectively infected in SIV and HIV [1,[40][41][42]. Combined these observations support our earlier data suggesting that DP T cells in the intestine are rapidly eliminated in early SIV infection due to their increased expression of viral co-receptors and their higher level of activation [1].…”
Section: Discussionsupporting
confidence: 86%
“…Higher expression of activation markers (HLA-DR, CD69 and CD25) has previously been reported on intestinal CD4 + T cells from neonatal and adult macaques [1,39]. Intestinal DP T cells also had higher expression of CCR5.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…164,165 It has been also reported that T-cell depletion in peripheral blood during primary infection was related to T cells expressing CCR5. [166][167][168] However, this latter observation remains controversial. 169 Since HIV-1 does not replicate efficiently in non-human primate species, chimeric simian-human immunodeficiency viruses (SHIVs) have been created that can infect NHPs.…”
Section: Cell Cycle Dysregulationmentioning
confidence: 99%